DINAMIKA RANTAI PASOK BERAS DI KECAMATAN BANSARI KABUPATEN TEMANGGUNG - Palupi, Aprillia; Priyanto, Sony Heru; Sunaryanto, Lasmono Tri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2020)
Temanggung Regency is the rice producer with the third highest productivity in the province of Central Java. Bansari District, one of the sub-districts in Temanggung Regency, has the potential to be developed as an agricultural area because most of its people are farmer. The study of rice supply chain in Bansari sub-district Temanggung regency is significance in order to design the efficiency of rice supply chain mechanism in the interest of rice farmers’ welfare in Bansari district Temanggung. The purpose of this research is to examine and review the patterns or mechanisms of rice supply chain and to analyse the role undertaken by the supply chain actors in Bansari district. The research method used a qualitative method. Data were collected through observation, interviews, documentation and library studies. The observed units in this research were the rice supply chain agents in Bansari subdistrict, namely rice farmers, rice milling entrepreneurs, rice traders and buyers or consumers of rice. The pattern of the rice supply chain actors in Bansari subdistrict, had only one supply chain flow, namely, the flow of products. There were several actors involved in the rice supply chain including farmers, active and passive traders, piners, milling, consumer households. The supply chain actors had their respective role in distributing rice from farmers to household consumers through the their relevant activities. There is no government intervention in supply chain in Bansari district. Business partnerships were required to develop businesses in the field of rice farming in Bansari district.